Photocatalytic degradation of Dichloroacetic acid: a kinetic study with a mechanistically based reaction model - Ballari, Maria de Los Milagros (2009)
In the present work, a study of the reaction kinetics of the photocatalytic degradation of dichloroacetic acid (DCA) employing UV radiation and titanium dioxide suspensions is reported. This study involved the development of a kinetic model from a proposed complete reaction sequence and estimation of the kinetic parameters from experimental data. The experimental data were obtained using a perfect mixed photoreactor, because the operating conditions were chosen in compliance with restrictive conditions established in a previous work in which the possibility of mass-transfer limitations in slurry reactors was investigated. The significant variables in this study were (1) the initial DCA concentration, (2) the catalyst loading, and (3) the light intensity. Simulation results from the complete reactor mass balance, including radiation transport in the bulk and resistances inside the catalytic particle agglomeration, are in good agreement with  experiments, which provides confidence in the estimation of the kinetic parameters within the range of the explored variables.